2020
DOI: 10.1002/ejic.201901043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity and Biological Effects of Heteroleptic N‐Heterocyclic Carbene Gold(I)‐Alkynyl Complexes

Abstract: With the aim to explore the effects of different organometallic ligands on the reactivity and biological properties of a series of twelve heteroleptic AuI complexes, of general formula [Au(NHC)(alkynyl)] (NHC = benzimidazolylidene or 1,3‐dihydroimidazolylidene) were synthesized and characterized by 1H and 13C NMR and elemental analysis, and in some cases also by X‐ray diffraction. The compounds were all stable in H2O/DMSO as established by NMR spectroscopy, while they could react with model thiols (EtSH) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…The present study aims at extending the investigation to different families of Au I and Au III compounds to identify possible structure–activity relationships. Thus, nine gold compounds, previously characterized for their anticancer effects, were synthesized according to reported procedures, including Au I mono‐ and bis‐NHC complexes ( 1 – 4 ), [23–25] Au III complexes coordinated to a bidentate NN scaffold ( 5 , 6 ), [26,27,28] and three cyclometallated Au III complexes with CN ligands ( 7 – 9 ) [29,30,31] (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…The present study aims at extending the investigation to different families of Au I and Au III compounds to identify possible structure–activity relationships. Thus, nine gold compounds, previously characterized for their anticancer effects, were synthesized according to reported procedures, including Au I mono‐ and bis‐NHC complexes ( 1 – 4 ), [23–25] Au III complexes coordinated to a bidentate NN scaffold ( 5 , 6 ), [26,27,28] and three cyclometallated Au III complexes with CN ligands ( 7 – 9 ) [29,30,31] (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…As seen in other NHC-Au-acetylides, the bond between the gold atom and the alkynyl ligand of 5a – 5e is slightly shorter than that to the carbene, however still within the margins of acceptable Au-C bond lengths [ 14 ]. The C-C bond lengths of the alkyne (C 30 -C 31 ) in the 1.193(6)–1.217(7) Å range are characteristic of a triple bond [ 27 ].…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, an iodido analogue of auranofin was shown to exhibit greater cytotoxicity than both auranofin and cisplatin against the human ovarian cancer cell line A2780 [ 12 ]. Alkynes are another ligand class often seen in gold(I) complexes, however only a handful of NHC-gold(I)-acetylides synthesised have been tested for their biological properties [ 13 , 14 , 15 ]. Mostly, gold(I)-acetylides are studied for their photophysical properties [ 16 ], although there are examples of phosphine-gold(I)-acetylides displaying high cytotoxicity against selected cancer cell lines [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Different classes of Au complexes have been evaluated to date; (i) neutral linear auranofin-type phosphane complexes, (ii) tetrahedral cationic Au(I) phosphane complexes, usually containing chelating bis(phosphane) ligands, (iii) linear Au(I) N-heterocyclic carbene (NHC) complexes and (iv) squareplanar Au(III) complexes. [9][10][11][12][13][14][15][16][17][18] Recently a few [Au(I)(alkynyl) (phosphane)] complexes have been reported that showed promising in vitro and in vivo activities, although their number has remained small compared to other gold complexes. [19][20][21][22][23] Here we report alkynyl phosphane and alkynyl NHC Au(I) complexes where the alkynyl ligand is a derivative of the quinazoline carboxamide class of ligands that bind to the translocator protein 18 kDa (TSPO).…”
Section: Introductionmentioning
confidence: 99%
“…Calc. (%) for C18 H 13 N 3 O (287.10): C, 75.25; H, 4.56; N, 14.63. Found (%): C, 75.20; H, 4.55; N, 14.59.…”
mentioning
confidence: 99%